Critical discourse analysis : the critical study of language - Fairclough, Norman, 1941- (Harlow : Longman, 2010)
Fairclough presents an interdisciplinary approach to the study of discourse viewing language as a form of social practice and focusing on the ways social and political domination are reproduced by text and talk. He provides an historical overview to this important discipline and concentrates on cutting-edge research in the field
Includes bibliographical references and index
Keywords: Discourse analysis; Sociolinguistics